2023
DOI: 10.3390/min13070845
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Aggregate Material Formulated with MSWI Fly Ash and Fuel Ash for Use as Filter Media

Abstract: This study aimed to develop a novel filtering medium ceramic aggregate prepared using municipal solid waste incineration (MSWI) fly ash and the fuel ash from coal power plants, together with small amounts of silicon carbide foaming agent and magnesia flux as additives. For the manufacturing process, the dosage of MSWI fly ash and the sintering temperature were optimized to maximize the performance of the resulting materials. Leaching test results indicated that the heavy metal concentrations in the ceramic agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Shao et al [21] developed a non-sintered fly ash filter material with sludge as an additive and studied the impact of pH on the adsorption efficiency of ammonium nitrogen in wastewater. In other research, Lu et al [22] demonstrated the use of another novel material-prepared using municipal solid waste incineration (MSWI) fly ash and the fuel ash from coal power plants, together with small amounts of silicon carbide foaming agent and magnesia flux as additives. These media have high efficiency in removing contaminants from wastewater, but their production requires thermal treatment, which results in high costs.…”
Section: Introductionmentioning
confidence: 99%
“…Shao et al [21] developed a non-sintered fly ash filter material with sludge as an additive and studied the impact of pH on the adsorption efficiency of ammonium nitrogen in wastewater. In other research, Lu et al [22] demonstrated the use of another novel material-prepared using municipal solid waste incineration (MSWI) fly ash and the fuel ash from coal power plants, together with small amounts of silicon carbide foaming agent and magnesia flux as additives. These media have high efficiency in removing contaminants from wastewater, but their production requires thermal treatment, which results in high costs.…”
Section: Introductionmentioning
confidence: 99%